Boreal Agriculture Cannot Be Sustainable Without Food Sovereignty - Keske, Catherine (Frontiers in Sustainable Food Systems, 2021)
• Food sovereignty encompasses the right of humans to have access to, and to produce, healthy and culturally appropriate food. • Food sovereignty exists within the “social” pillar of sustainability and sustainable food production. • Over time, and as a result of colonialism and neo-liberal food regimes, Indigenous food system patterns in boreal regions have been disrupted. Imports make local food production economically infeasible. • The intersection of food sovereignty and international trade is understudied. Food insecurity cycles are likely to perpetuate without deliberate action and government intervention. • Policies that facilitate local access, and ownership, of agriculture and food processing facilities may foster food sovereignty. • Indigenous community governance, and agricultural practices, are critical to restoring environmental and social sustainability.